1981
DOI: 10.1136/oem.38.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory function in Nigerian coal miners.

Abstract: Ventilatory capacity has been measured in 675 Nigerian colliery employees classified in three groups according to occupation: coalface workers, other underground workers with low exposure to dust, and surface workers in administrative and clerical jobs. Men with current respiratory symptoms were excluded, as were ex-miners. The faceworkers were a slightly older group who smoked less, and they were presumed to be more active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Also Jain B.L. (1981) [12] reported that coalface work is associated with 8% impairment of maximum expiratory airflow, probably due to dust exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Also Jain B.L. (1981) [12] reported that coalface work is associated with 8% impairment of maximum expiratory airflow, probably due to dust exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Although this result may have been influenced by survivor sample bias, it suggests that in that coal field, accelerated rates of decline may be uncommon. Jain and Patrick [1981] reported an average rate of FEVl decline of -34 ml/yr in 675 Nigerian underground miners.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies on the association between coal mining and lung function have been carried out in developing countries in Africa. A study from Nigeria showed that FEV 1 did not vary among occupational groups in the colliery (Jain and Patrick 1981).…”
Section: Introductionmentioning
confidence: 98%